A selected review of abstracts from the 4th Quadrennial Meeting of the World Federation of Neuro-oncology. (March 2014) - Chamberlain, Marc C
The 4th Quadrennial Meeting of the World Federation of Neuro-Oncology (WFNO), San Francisco, CA, USA, 21–24 November 2013 The 4th Quadrennial Meeting of the World Federation of Neuro-Oncology (WFNO) was the largest neuro-oncology meeting that meets once every 4 years and brings together clinicians and scientists from all parts of the world whose focus is on new brain cancer clinical trials and research primarily pertaining to gliomas. The WFNO 2013 meeting included 1 education day, 2.5 days of presentation, 13 sunrise sessions, one town hall meeting, one mini-symposium, 130 oral presentations and 900 abstracts. This short meeting review highlights select adult clinical abstracts presented at WFNO 2013 that will only in part encompass the contents of a large and multifaceted meeting.